MAKING SENSE OF THE LABOUR MOVEMENT AS WE CONFRONT THE BURDEN OF THE FUTURE - Marks, Monique (New Agenda: SA Journal of Social and Economic Policy, 2024)
While celebrating the ‘Durban Moment’ we shoudl also reflect on new challenges and opportunities facing the labour movement in South Africa presently. This requires a blunt honesty and a perspective that does not rely on nostalgia. To do this we need to step out of dominant narratives and political correctness, and demystify where South African youth find themselves in present day South Africa. This article is written as a provocation for those in the labour movement and the allies of labour. This paper reflects on the changed landscape of youth politics in South Africa – from apartheid to close to thirty years post-apartheid. This provides a lens for sense making how the labour movement should be responding to the multiple crises facing young peple in contemporary South Africa. I use the term ’burden of the future’ to describe and analysse the state that young people find themselves in - one with little hope of access to social institutions or a decent life. Conventional labour strategies are ill-equiped to deal with this social reality in their present form. This paper was presented at the final session of the 1973 Durban Strikes 50th Remembrance held at the Durban University of Technology